Penerapan Metode Pelayanan BK Pada Siswa SMA Muhammadiyah 1 Surakarta - Anisa Indriyani; Qanita Alifatul Azzahra; Dhian Rizkiana Putri (BADAN PENERBIT STIEPARI PRESS, 2024)
Guidance and Counseling Services is a part of the education sector with the task of helping the effectiveness of students' lives based on the harmony of adolescent development tasks. Guidance and Counseling is the provision of assistance carried out through counseling interviews by expert people (counselors) to individuals who experience a problem with the aim of solving the problem and allowing the individual to utilize their potential, so that the individual can understand himself to achieve optimal, independent and independent development. can plan the future. The method of this service is carried out with classical services in the classroom during guidance and counseling hours as well as individual services carried out in the counseling room in the BK room. The conclusion in this service is that classical guidance and counseling services with fun methods can attract students' attention to listen and understand the material presented and individual guidance and counseling services with closed and confidential methods make students more comfortable to be open in telling their problems.